RENOVATION OF SYSTEMS AND TECHNOLOGIES TO MAKE PRODUCTION AS AN EFFECTIVE REGIONAL MANAGEMENT CONDITION - M. Zaharov, Viktor; V. Bykhtyn, Oleg; I. Gulyaev, Ivan; V. Shevchenko, Natal’ya; N. Shmigirilova, Larisa; N. Yurkova, Olga (Gênero & Direito, 2020)
The article studies the orientation of professional potential of improving technologies with the goal of making production as an effective way to ensure the effectiveness of regional management, discloses the mechanisms for management professional potential transformation into the indicators of its effectiveness and efficiency. They provided the data of the sociological study "Professional potential reproduction system development among regional management personnel”. The result of the study in this direction was the developed cumulative technology for computer assessment of the competence potential among regional management employees, which includes three blocks: assessment unit, planning unit, and control (correction) unit.